PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN COCA-COLA (Studi Kasus Pada Mahasiswa Stiami Kampus Bekasi Angkatan 2018) - Indah Rahmadani; Abdul Gofur (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study was conducted to determine the effect of product quality and brand image on the purchase decisions for Coca-Cola (a case study on students of STIAMI, Bekasi Campus Class of 2018). This research is an explanatory research with a quantitative approach.The results of the study indicate that product quality has t count > t tablewhich is 3.282 > 1.98793 with a sig value of 0.001 < 0.05, which means that partially product quality has a positive and significant , effect on purchase decisions. Brand image has t count > t table , which is 4.647 > 1.9879 with a sig value of 0.000 < 0.05, which means that partially brand image has a positive and significant effect on purchase decisions. Meanwhile, simultaneously, product quality and brand image have an f count value of 44,876 with a significance level of 0.000, which means that both variables have a positiveand significant effect on purchase decisions.